2020 Physics Education Research Conference Proceedings 2020
DOI: 10.1119/perc.2020.pr.fields
|View full text |Cite
|
Sign up to set email alerts
|

The transition to online teaching during the COVID-19 pandemic at a regional, rural university: The experience of learning assistants

Abstract: During the Spring 2020 semester, classes at a medium-sized regional rural university transitioned from faceto-face (FTF) to fully online instruction following Spring Break due to the COVID-19 pandemic. Learning assistants teaching in STEM disciplines experienced difficulties during this transition unique to our student population consisting of many nontraditional and first generation students living in rural areas. We conducted a phenomenological study about these LAs experiences using a Community of Practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…LAs, on the other hand, are interacting with individual students and may provide increased informational support to students who are less engaged. If LA informational support does not shift student engagement, which may have been harder to do in the remote setting as students encountered more distractions, then the pattern we observed could be the result. An alternative hypothesis is that LAs’ experience level influences the types of messaging that they provide to students.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…LAs, on the other hand, are interacting with individual students and may provide increased informational support to students who are less engaged. If LA informational support does not shift student engagement, which may have been harder to do in the remote setting as students encountered more distractions, then the pattern we observed could be the result. An alternative hypothesis is that LAs’ experience level influences the types of messaging that they provide to students.…”
Section: Discussionmentioning
confidence: 84%
“…One explanation for this may be that students in the remote synchronous courses found it more challenging to remain engaged. Studies on students during the transition to online teaching during COVID have found that they overall had lower engagement in their courses, , and they reported experiencing more distractions and conflicting responsibilities . Additional studies found students had to overcome several emotional, cognitive, and practical barriers to remain engaged in their coursework. , As students struggle to focus in their remote classes, social support from LAs and course instructors might be more critical to student engagement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations